1963
DOI: 10.1149/1.2425747
|View full text |Cite
|
Sign up to set email alerts
|

Stresses in Anodic Films

Abstract: Stresses in anodic films produced on several metals were measured by clamping the upper end of a thin foil of the metal and observing the motion of the lower end through a telescope. 1 Foils were about 10 cm long, and one side was coated with stopcock grease to prevent anodization. (Grease is preferable to lacquer which shrinks on drying and can support some stress.) Deflections were of the order of a millimeter in most experiments; the minimum measurable deflection was about 0.005 cm. No twisting of the foil … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
67
0

Year Published

1973
1973
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(75 citation statements)
references
References 1 publication
6
67
0
Order By: Relevance
“…9,11,18,21 Both Vermilyea and Bradhurst observed transitions from compressive to tensile stress with increasing current density. Other studies of porous anodic alumina growth found the same trend.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…9,11,18,21 Both Vermilyea and Bradhurst observed transitions from compressive to tensile stress with increasing current density. Other studies of porous anodic alumina growth found the same trend.…”
Section: Resultsmentioning
confidence: 96%
“…[14][15][16][17] Like the materials in these experiments, anodic alumina films are amorphous, and stresses large enough to drive significant creep ͑10-100 MPa͒ are found during the growth of both porous and planar anodic alumina. 9,11,[18][19][20][21] Stresses during anodizing may arise from volume constraints at the metaloxide interface, and from electrostatic forces in the oxide dielectric. [22][23][24] In this paper, we present a model for transport in planar anodic films by coupled electrical migration, plastic flow, and migration in the stress field.…”
mentioning
confidence: 99%
“…Hence, the tensile shift was attributed to processes within the anodic oxide. Vermilyea and Wüthrich suggested that the tensile stress change is due to dehydration of the outer hydrated portion of the oxide, 7,13 and Bradhurst and Leach ascribed it to removal of electrostatic stress. 21 These explanations cannot be valid in view our findings that the tensile open circuit force increases with anodizing current density (Fig.…”
Section: Implications Of the Stress Measurements-mentioning
confidence: 99%
“…Thus, without consideration of transport numbers, the densities of anodic oxide and metal phases typically suggest that large compressive stress should be produced, while instead tensile stress may be observed during anodizing of metals such as Al where the metal ions transport appreciable current [54]. Other stress-producing reactions may include hydration/dehydration of the oxide near the solution interface [55,56] and interfacial reactions that produce or consume point defects (as interstitials and vacancies contribute lattice expansion and contraction, respectively) [57,58]. Anodic oxides also exhibit electrostriction stress, that is, elastic stress balancing electrical forces on the dielectric oxide material [59].…”
Section: Phenomenology Of Porous Anodic Oxide Formationmentioning
confidence: 99%